(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Internationally, the use of Value Added Tax zero-rating to lessen the tax’s regressivity is now widely acknowledged. From an economic point of view, it is still debatable if zero-rating is the most economical method of helping the poor. The 2018 1% VAT rate increase in the South African tax system has renewed focus on the need of zero-rating from the viewpoints of equality and poverty. This paper evaluated whether the existing list of commodity items with zero ratings improves welfare and whether or not more items should be taken into consideration for potential zero-rating. The Southern Africa Labour and Development Research Unit’s National Income Dynamics Survey (2018) of South Africa was used in this study. The survey offered pertinent data on family spending on specific items by total spending and income level. The study’s conclusions showed that a fair and just tax system required the VAT zero-rating of particular items as a logical and essential step. Most of the items with a zero rating are used by low-income households. However, there are a few exceptions to the rule for fruits and some vegetables. Also, the study commends individually quick-frozen (IQF) chicken portions for zero-rating. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 401-415